2008
DOI: 10.1002/jso.21094
|View full text |Cite
|
Sign up to set email alerts
|

Elevated p21 expression is associated with poor prognosis of rectal stromal tumors after resection

Abstract: Elevated p21 expression is associated with poor prognosis of rectal stromal tumors after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…The results showed that the expression of p21 (P=0.0222) and p27 (P=0.2777) negatively correlated with prognosis, however, this was not statistically significant for p27. The present study demonstrated that the five-year survival rate of patients with a p21 expression score of >2.7 was significantly lower when compared with that of patients with a score of ≤2.7, inconsistent with the majority of previous studies in OSCC (10,11) and other types of cancer (2934). However, certain other controversial results have also been reported (3537).…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that the expression of p21 (P=0.0222) and p27 (P=0.2777) negatively correlated with prognosis, however, this was not statistically significant for p27. The present study demonstrated that the five-year survival rate of patients with a p21 expression score of >2.7 was significantly lower when compared with that of patients with a score of ≤2.7, inconsistent with the majority of previous studies in OSCC (10,11) and other types of cancer (2934). However, certain other controversial results have also been reported (3537).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, elevated p21 expression correlated with diminished survival of esophageal squamous cell carcinoma patients with mutations in the p53 gene [33]. Correspondingly, p21 expression was also associated with poor prognosis of patients with rectal stromal tumors after resection [34] and induction of p21 during anticancer treatment in patients with rectal carcinoma was correlated with the development of resistance to neoadjuvant radiochemotherapy, with worse outcome of the disease [35].…”
Section: P21 As An Oncogenementioning
confidence: 99%
“…Finally, 14 articles published from 1995 to 2017 with 1372 patients is in line with the criteria for meta-analysis. [814,2329] The detailed process of study selection is presented as a flowchart in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%